Comparison of two paradigms based on stimulation with images in a spelling brain-computer interface. - Ron-Angevin, Ricardo; Beasse, Joseph; Clément, Adrien; Dupont, Clara; Le Gall, Maiwenn; Meunier, Juliette; Lespinet-Najib, Véronique; André, Jean-Marc (IARIA, 2022)
A BCI Speller is a typical Brain-Computer Interface (BCI) system for communication purposes. This technology can provide users with severe motor disability with an assistive device controlled by brain activity. The present preliminary study, with only four subjects, is focused on the control of a 5x5 P300-based speller matrix for communication purposes. In this work, we study the effect of flashing stimuli used to highlight the letters in two conditions: pictures and red famous faces (that is, famous faces coloured in red). These preliminary results, based on performance and the Information Transfer Rate (ITR), showed that both conditions are similar, obtaining very good performance compared to conventional P300-speller. In this sense, the use of pictures does not make the performance worse, allowing to develop more attractive and usable interfaces. More tests would confirm if there is a difference in performance between the two conditions proposed.
Keywords: Interfaces de ordenadores; Estimulacion nerviosa; Movimiento; Cerebro; Interacción hombre-ordenador; Brain-Computer Interface (BCI); P300; RCP paradigm; Speller; Stimuli; RCP paradigm